PENGARUH KOMPETENSI, KOMPENSASI TERHADAP PRODUKTIVITAS KARYAWAN PADA KOPI TJAN, KAYU PUTIH JAKARTA TIMUR - Nur Zhafirah Ali Chaniago; Bulan Azizah Mokodompit; Praditio Al Fajri; Ilman Nurdin Adha; Ratih Ayu Sekarini; Dhita Puspita Rini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Workplace productivity at Kopi Tjan, Kayu Putih Branch is affected by factors such as staff competency and pay rate. A quantitative methodology of the causal associative research type was used in the investigation. All 54 workers were chosen using a saturation sample approach, and data was acquired via observations and questionnaires. The data was analyzed using SPSS version 25, which included tools for hypothesis testing (t-test and F-test), multiple linear regression analysis, classical assumption tests, and the coefficient of determination. The study's findings indicate that, at a significance level of 0.923 and a t-count value of -0.098, the competence variable somewhat influences employee productivity in a favorable but non-significant way. At the same time, a t-count value of 5.234 and a significance level of 0.000 show that the remuneration variable has a positive and significant influence on employee productivity. With an F-count value of 24.620 and a significance level of 0.000, competence and salary both significantly impact employee productivity. With a R Squared value of 0.491, Researcher can see that the competence and compensation variables account for 49.1% of the variance in productivity, while other factors impact the remaining portion. In order to keep employees productive, the organization should examine its training programs often and try to improve its remuneration structure.